An improved effective medium model for the electrical properties of granular rocks accounting for grain contact. Issue 1 (29th November 2022) - Han, Tongcheng; He, Haiming; Fu, Li-Yun
SUMMARY: Differential effective medium (DEM) model has been widely employed for the interpretation of electrical survey data. However, the contact of grains that is inevitably happening in reservoir rocks is not taken into account by the DEM model, making the model prediction underestimate the measured formation factor of clean granular rocks. We have developed a modified DEM model by introducing a geometric factor to account for the contact of grains that complicates the pore network and thus deviates the transportation of electrical current. The geometric factor is derived by fitting the measured formation factor from a large published data set of 111 clean sandstone samples, and is found to decrease exponentially with rock porosity. Comparison with laboratory data sets of various artificial and real clean sandstones shows that the modified DEM model improves the modelling results and fits satisfactorily the measured formation factor with varying porosity. The results illustrate the practical applicability of the developed closed-form model for the improved simulation of electrical properties of clean granular rocks, and suggest grain contact as a potential link for the joint elastic-electrical characterization of granular rocks through integrated seismic and electromagnetic surveys.